It’s All Up to My Fellow Citizens. Descriptive Norms as a Decisive Mediator in the Relationship Between Infrastructure and Mobility Behavior - Rollin, Philipp; Bamberg, Sebastian (Frontiers in Psychology, 2021)
Following the implementation of temporary pop-up-bike-lanes in Berlin, traffic counts by the city administration show an increased number of cyclists. This present paper aims to understand reasons behind this observation. To this end, we focus on the role of mobility-related descriptive social norms as mediators of this effect. Results from one correlational and two experimental online studies are reported. The correlational study confirms the expected association of mobility-related descriptive social norms and self-reported mobility behaviour. Moreover, it demonstrates, that, as expected, mobility-related descriptive social norms reliably reflect differences in cities’ objective transport structure and mediates the impact of these infrastructural differences on mobility behaviour. Results from two online experiments provide additional causal evidence that participants use the visual cues provided by manipulated photos to form their perceived mobility-related descriptive social norms. Furthermore, the second online experiment provides evidence that the combination of infrastructural cues and observable mobility behaviour has the strongest impact on perceived mobility-related descriptive social norms.